CERAMIC MATERIAL FROM SEWAGE SLUDGE AS SUPPORT MATERIAL SUPPLY WATER FILTRATION - Morais, L. C. [UNESP]; Rosa, André Henrique [UNESP]; Fraceto, L. F. [UNESP]; Toledo, A. C. T.; Campos, V. [UNESP] (Trans Tech Publications Ltd, 2012)
This study shows a possibility of using municipal sewage sludge after thermal treatment in the production of a filtering material to water treatment. Due to the fast urbanization and implementation of high standards for effluent in many countries in recent years, the sewage sludge is being produced in an ever increasing amount. Therefore, the use of sludge is a suitable solution for the expected large quantity of sludge. Dehydration of sludge was performed by controlled heating at temperatures of 1100 degrees C, 850 degrees C, 650 degrees C, 350 degrees C for 3 hours. After thermal treatment the sludge was characterized by X-ray fluorescence, TG/DTG/DTA, residue solubilization and residue lixiviation tests. The aim of the present work was to observe, thought the characterization techniques, if the treated sewage sludge is or not adequate to be used as filter material to water treatment. It will be verified which treatment temperature of the sludge offer possibility to its use in water treatment without carrying pollutants in concentrations out of the standards.
Keywords: support material; water filtration; water soluble; leaching